Percentage of haemoglobin variants detected during HbA1c analysis in Hospital Kuala Lumpur - Samsudin, Intan Nureslyna; Md Noor, Sabariah; Lim, C. R.; Wan Salleh, Wan Nor Syafiqah; Chen, D. R.; Choy, S. Y.; Othman, Nor'Ashikin (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2013)
HbA1c is an established index of glycaemic control and correlates strongly with risk of chronic diabetic complications. However, the accuracy of HbA1c measurement can be affected by many factors, among which is the presence of haemoglobin (Hb) variants. The aim of the study was to determine the percentage of Hb variant detected during HbA1c monitoring in Hospital Kuala Lumpur. The study also analysed non-reportable HbA1c results in the presence of Hb variants. A cross-sectional study using retrospective data of HbA1c results over five months’ period was analysed on Biorad Variant II Turbo, a high performance liquid chromatography (HPLC) assay. The Hb variants were grouped either as HbS, HbC, others (Hb variant apart from HbS or C), and a combination of HbS or C with Others. A total of 11,904 patients were included. Only 2.3% (273) had Hb variants; HbS trait (10.3%), others (89%), and the combination of HbS trait with others (0.7%). No patient with HbC variant or its combination was found. Only 2.2% of those with Hb variant had non-reportable HbA1c. Although the percentage of Hb variants detected during HbA1c analysis and non-reportable HbA1c results were low, their presence should be noted.